Risk of death and readmission of hospital-admitted COPD exacerbations: European COPD Audit. Issue 1 (22nd October 2015) - Hartl, Sylvia; Lopez-Campos, Jose Luis; Pozo-Rodriguez, Francisco; Castro-Acosta, Ady; Studnicka, Michael; Kaiser, Bernhard; Roberts, C. Michael
Studies report high in-hospital and post-discharge mortality of chronic obstructive pulmonary disease (COPD) exacerbations varying depending upon patient characteristics, hospital resources and treatment standards. This study aimed to investigate the patient, resource and organisational factors associated with in-hospital and 90-day post-discharge mortality and readmission of COPD exacerbations within the European COPD Audit. The audit collected data of COPD exacerbation admissions from 13 European countries. On admission, only 49.7% of COPD patients had spirometry results available and only 81.6% had blood gases taken. Using logistic regression analysis, the risk associated with in-hospital and post-discharge mortality was higher age, presence of acidotic respiratory failure, subsequent need for ventilatory support and presence of comorbidity. In addition, the 90-day risk of COPD readmission was associated with previous admissions. Only the number of respiratory specialists per 1000 beds, a variable related to hospital resources, decreased the risk of post-discharge mortality. The European COPD Audit identifies risk factors associated with in-hospital and post-discharge mortality and COPD readmission. Addressing the deficiencies in acute COPD care such as making spirometry available and measuring blood gases and providing noninvasive ventilation more regularly would provide opportunities to improve COPD outcomes. Hospital-admitted COPD exacerbation needs better risk stratification: spirometry and gas analysis improve outcomes http://ow.ly/RTbdk